2010
DOI: 10.1007/s11999-010-1306-8
|View full text |Cite
|
Sign up to set email alerts
|

Nonadherence in Outpatient Thrombosis Prophylaxis with Low Molecular Weight Heparins after Major Orthopaedic Surgery

Abstract: Level II, prognostic study. See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
4
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 45 publications
2
42
4
1
Order By: Relevance
“…Over Despite major efforts to ensure systematic implementation into clinical practice (32,36), our results also demonstrated that adherence to ACCP guidelines has decreased significantly over the last 10 years and the gap between the guidelines recommendations and their implementation in clinical practice is still present (5,(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 64%
“…Over Despite major efforts to ensure systematic implementation into clinical practice (32,36), our results also demonstrated that adherence to ACCP guidelines has decreased significantly over the last 10 years and the gap between the guidelines recommendations and their implementation in clinical practice is still present (5,(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 64%
“…The available evidence shows that self-reporting underestimates the extent of NA [61][62][63][64]. In this regard, the inclusion of other indicators such as administrative data or Medication Event Monitoring System/pill counts would considerably increase the validity of the NA measurement [34,65,66]. Limited data availability, however, is the challenge here.…”
Section: Discussionmentioning
confidence: 99%
“…In the first survey, 1177 patients were interviewed by a structured telephone interview. This survey was originally conducted to assess the extent of NA in outpatient thromboprophylaxis after major orthopedic surgery [34]. The interviewed patients were drawn from 22 German acute or rehabilitation orthopedic clinics (informed consent).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Education has also been considered an important aspect to enforce VTE prophylaxis [7]. This has been shown to improve patient outcomes and adherence [18,19].…”
Section: Transition Into the Outpatient Settingmentioning
confidence: 99%